Innovation-based Human Resources Performance Improvement Strategy to Support Tourism Recovery at Tourism Village - Verawati, Dian Marlina; Achsa, Andhatu; Novitaningtyas, Ivo (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim: This study aims to analyze the internal and external factors of human resource performance in order to formulate a strategy to improve human resource performance based on innovation in tourism villages in the Magelang area Design/Methode/Approach: This research uses a descriptive qualitative approach. Primary data were obtained based on interview data collection methods and participatory observation. SWOT analysis was used as the data analysis method. Research Finding: The results showed strategy formulations to improve human resource performance. The proposed strategies become an effort to restore tourism activities in the new normal era after Pandemi Covid-19. Theoretical contribution/Originality: This study identified the internal and external conditions of human resources based on innovation factors. Practitioner/Policy Implication: The results give implications to the manager in order to improve human resource performance including increasing the intensity of human resource training and development programs, increasing the competence of human resources to innovate and create an integrated tour package according to the needs of tourists, providing adequate health facilities for human resources, increasing cooperation with other tourism actors, and make a long term of human resource development planning based on innovation. Research limitation: This research conducted limited on the tourism villages in the Magelang area as a tourism object. Further research can develop other tourism areas with different characteristic to expand research benefits.